Analisis Kesalahan Siswa dalam Menyelesaikan Soal Persamaan dan Pertidaksamaan Nilai Mutlak Berdasarkan Teori Newman - Cahyaningtyas, Octavita; Rahardi, Rustanto; Irawati, Santi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The purpose of this study is to describe the types of errors that students make in solving absolute value equations and inequalities using Newman's theory (NEA). The method used in this study is a qualitative descriptive method. Questions were given to 30 students of class X SMA Negeri 1 Sumberpucung. The data collection techniques in this study were the results of students' written tests and the results of interviews related to the results of students' written tests. Based on the results of the research conducted, it is known that there are no students who experience reading errors on all questions while encoding error in answers are the mistakes that most students make. This happens because when students make mistakes in understanding, students will automatically make mistakes in understanding, transforming, processing skill and encoding error. The mistakes that students make are based on their lack of understanding of the concept of absolute value. Because if students understand the existing concepts correctly, they will be able to solve various existing problems. So that teachers are advised to provide meaningful learning for students so that students do not easily forget the concept of a material. From this research, it can be concluded that the types of errors that students make are understanding, transforming, processing skill and encoding error.